Integrated life-cycle analysis of six insulation materials applied to a reference building in Portugal - Saadatian, Seyedeh Shiva (2014)
Dissertação de Mestrado em Energia para a Sustentabilidade apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra